2017
DOI: 10.1186/s12879-017-2544-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic scoring model for Mycobacterium avium complex lung disease: an observational cohort study

Abstract: BackgroundPatients with Mycobacterium avium complex (MAC) lung disease (LD) have a heterogeneous prognosis. This study aimed to develop and validate a prognostic scoring model for these patients using independent risk factors for survival.MethodsWe retrospectively analyzed the data of patients with MAC-LD from two hospitals (cohort 1, n = 368; cohort 2, n = 118). Cohort 1 was evaluated using a multivariate Cox proportional hazards model to identify independent risk factors for overall survival (OS). A prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 21 publications
5
35
1
Order By: Relevance
“…Predictors of high mortality included male gender, presence of comorbidities, and fibro cavitary disease. These findings have been validated in other studies that showed that male patients, with fibro cavitary disease, low BMI and malignancy were prognostic indicators of poor clinical outcome (41,119,120). In addition, patients with persistent infection (those who remain culture positive despite 12 months of treatment) have higher rates of death attributable to NTM infection compared to those who manage to clear NTM in the sputum (34).…”
Section: Recent Developments and Research Prioritiessupporting
confidence: 58%
“…Predictors of high mortality included male gender, presence of comorbidities, and fibro cavitary disease. These findings have been validated in other studies that showed that male patients, with fibro cavitary disease, low BMI and malignancy were prognostic indicators of poor clinical outcome (41,119,120). In addition, patients with persistent infection (those who remain culture positive despite 12 months of treatment) have higher rates of death attributable to NTM infection compared to those who manage to clear NTM in the sputum (34).…”
Section: Recent Developments and Research Prioritiessupporting
confidence: 58%
“…The progression of the cavity leads to destruction of the lungs, which results in respiratory failure and poor prognosis. Unlike previous studies [6][7][8][9] that assessed prognostic factors but yielded recommendations that were somewhat complicated to apply in daily clinical practice, our results indicate that the combination of two simple findings can predict disease Fig. 2 Rates of progressive cavities stratified by maximum inner diameter and consolidation around the initial cavity.…”
Section: Discussioncontrasting
confidence: 60%
“…Poor prognostic factors for MAC-PD include old age, low body mass index (BMI), low lung function, anemia, high blood deposition, malignancy, and hemosputum. Notably, the presence or absence of cavities is the most important factor [6][7][8][9]. Enlarged progressive cavities destroy lungs, leading to respiratory failure and poor prognosis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…That decision is not difficult for cavitary MAC-LD patients because of the clear risk for disease progression and associated morbidity and mortality associated with cavitary MAC-LD. [15][16][17][18][19][20] Therefore, the risk/benefit evaluation unambiguously favors initiating therapy at the time cavitary MAC-LD is diagnosed. For patients with NB MAC-LD, that decision is not as straightforward and requires a more deliberate approach.…”
Section: Deciding Which Patients To Start On Mycobacterium Avium Compmentioning
confidence: 99%
“…Those NB MAC-LD patients not started on therapy must be followed up indefinitely as there is mounting evidence for significant risk of MAC-LD-associated morbidity and mortality in patients not started on antimycobacterial therapy. 18,[21][22][23][24] There are few objective markers of MAC-LD disease progression. A recent study compared the clinical characteristics of MAC-LD patients who had a progressive course resulting in treatment initiation within 3 years of diagnosis with patients who exhibited a stable course for at least 3 years.…”
Section: Deciding Which Patients To Start On Mycobacterium Avium Compmentioning
confidence: 99%